Clinical Impact and Healthcare Resource Utilization Associated with Early versus Late COPD Diagnosis in Patients from UK CPRD Database - Kostikas K; Price D; Gutzwiller FS; Jones B; Loefroth E; Clemens A; Fogel R; Jones R; Cao H (International Journal of COPD, 2020)
Konstantinos Kostikas,1 David Price,2 Florian S Gutzwiller,3 Bethan Jones,4 Emil Loefroth,3 Andreas Clemens,3,5 Robert Fogel,6 Rupert Jones,7 Hui Cao6 1Respiratory Medicine Department, University Hospital of Ioannina, Ioannina, Greece; 2Centre of Academic Primary Care, University of Aberdeen, Aberdeen, UK; 3Novartis Pharma AG, Basel, Switzerland; 4Pharmatelligence, Cardiff, UK; 5Department of Cardiology and Angiology I, Heart Center Freiburg University, Faculty of Medicine, University of Freiburg, Freiburg, Germany; 6Novartis Pharmaceuticals Corporation, East Hanover, NJ, USA; 7Plymouth University Peninsula School of Medicine and Dentistry, Plymouth, UKCorrespondence: Konstantinos KostikasRespiratory Medicine Department, University Hospital of Ioannina, Ioannina, GreeceEmail ktkostikas@gmail.comPurpose: Previous studies have shown that opportunities to diagnose chronic obstructive pulmonary disease (COPD) early are often missed in primary care. This retrospective study aimed to utilize secondary data from the United Kingdom (UK) healthcare system to understand the impact of early versus late diagnosis of COPD.Patients and Methods: Newly diagnosed COPD patients were identified in the UK Clinical Practice Research Database from 2011 to 2014. Patients whose 5-year medical data before diagnosis revealed ≥ 3 counts of eight indicators of early COPD were deemed as late-diagnosed, whereas others were deemed as early-diagnosed. We assessed patients’ characteristics; time-to-first, risk, and rates of exacerbation; and healthcare resource utilization (COPD-related clinic visits, Accident and Emergency visits, and hospitalizations) in late- versus early-diagnosed patients.Results: Of 10,158 patients included in the study, 6783 (67%) were identified as late-diagnosed and 3375 (33%) as early-diagnosed. The median time-to-first exacerbation was shorter in late-diagnosed (14.5 months) versus early-diagnosed (29.0 months) patients, with a significant risk of exacerbation (hazard ratio 1.46 [95% confidence interval: 1.38– 1.55]). Additionally, the exacerbation rate (per 100 person-years) over 3 years was higher in late (108.9) versus early (57.2) diagnosed patients. Late-diagnosed patients had a significantly higher rate of COPD hospitalizations (per 1000 patient years) compared with early-diagnosed patients during 2 and 3 years of follow-ups (P = 0.0165 and P < 0.0001, respectively).Conclusion: Results showed that a significant percentage of COPD patients in UK primary care are diagnosed late. A late COPD diagnosis is associated with a shorter time-to-first exacerbation and a higher rate and risk of exacerbations compared with early diagnosis. Additionally, late diagnosis of COPD is associated with a higher rate of COPD-related hospitalizations compared with early diagnosis.Keywords: chronic obstructive pulmonary disease, COPD, clinical practice research datalink, UK-CPRD, early diagnosis of COPD, late diagnosis of COPD, healthcare utilization